Developing a Creative Entrepreneurship Education Model to Enhance Student’s Creativity and Innovation for Successful Completion of the Independent Entrepreneurship MBKM Program - I Gusti Putu Bagus Sasrawan Mananda; Ni Putu Eka Mahadewi (Postgraduate, University of Mataram, 2023)
In this study, the objective is to develop an innovative educational model for fostering creativity and innovation in aspiring entrepreneurs using the